2004
DOI: 10.1055/s-2004-861497
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrovascular Risk Factors and Clinical Classification of Strokes

Abstract: Cerebrovascular risk represents a progressive and evolving concept owing to the particular distribution of risk factors in patients with ischemic stroke and in light of the newest stroke subtype classifications that account for pathophysiological, instrumental, and clinical criteria. Age represents the strongest nonmodifiable risk factor associated with ischemic stroke, while hypertension constitutes the most important modifiable cerebrovascular risk factor, confirmed by a host of epidemiological data and by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 50 publications
4
40
0
10
Order By: Relevance
“…The most important risk factors for stroke and cardiovascular disease are diabetes, hypertension, hyperlipidaemia and smoking. 18,19 Examining the relationship between traditional risk factors for cardiovascular disease and stroke might clarify the associations between CSF orexin-A concentrations and cerebrovascular infarction. Yuan et al 20 showed that orexin-A treatment can induce prominent neuroprotective effects on transient cerebral ischaemia in rats by improving neurological function and decreasing infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…The most important risk factors for stroke and cardiovascular disease are diabetes, hypertension, hyperlipidaemia and smoking. 18,19 Examining the relationship between traditional risk factors for cardiovascular disease and stroke might clarify the associations between CSF orexin-A concentrations and cerebrovascular infarction. Yuan et al 20 showed that orexin-A treatment can induce prominent neuroprotective effects on transient cerebral ischaemia in rats by improving neurological function and decreasing infarct size.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The same result was observed with serum hs-CRP, which has been suggested as an inflammatory parameter in patients with a cerebrovascular attack. 18,19,20 Because EPCs mobilization from bone marrow may occur following acute stroke, we hypothesized that the number of EPCs would change during the course of stroke. We therefore monitored circulating EPCs levels during the course of stroke progression.…”
Section: Discussionmentioning
confidence: 99%
“…Common comorbidities associated with stroke include aging, elevated blood pressure, and metabolic dysfunctions. These conditions are often associated with the exacerbation of ischemic outcomes and are predictive of worse recovery [186]. The inclusion of hyperlipidemia and diabetes in animal models of stroke has demonstrated that these conditions modulate postischemic inflammatory responses and lesion development [101,152,187,188].…”
Section: Modulatory Function Of Mononuclear Phagocytes In Comorbiditiesmentioning
confidence: 99%